PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) PADA MATA PELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA KELAS III UPTD SD NEGERI 190 BARRU - Putri Hamzah; Siti zalzabila ibrahim; Abdan Syakur (STKIP Subang, 2024)
This study aims to analyze the impact of implementing the Two Stay Two Stray (TSTS) cooperative learning model on mathematics learning outcomes among third-grade students at UPTD SD Negeri 190 Barru. Conducted as classroom action research (CAR), this study involved 20 students as participants. The research was carried out over two cycles, each comprising four stages: planning, action, observation, and reflection. The results revealed a significant improvement in students' performance. In Cycle I, only 9 students (45%) achieved the minimum passing grade (KKM) of 70, while 11 students (55%) did not. However, after refining the implementation of the TSTS model in Cycle II, 17 students (85%) met the KKM, leaving only 3 students (15%) below the threshold. This improvement demonstrates the effectiveness of the TSTS model in enhancing mathematics learning outcomes by promoting collaboration and active participation among students. The findings suggest that cooperative learning models like TSTS are beneficial for addressing challenges in teaching abstract subjects such as mathematics.